2000
DOI: 10.1001/archopht.118.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in Paintball Sport–Related Ocular Injuries

Abstract: To describe the type and severity of ocular injuries caused by paintballs, to summarize the outcomes, to determine if the injury occurred in a commercial or noncommercial setting, to compare the number of injuries in each setting as a function of time, and to ascertain whether eye-protective devices were worn and why they were removed. Design: Retrospective analysis of 35 patients who sustained ocular injuries caused by paintballs and underwent evaluation and treatment at an eye hospital from January 1, 1985, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 12 publications
0
29
0
1
Order By: Relevance
“…3,4 With 9.64 million paintball participants in the United States alone, paintball is the third most popular 'extreme' sport, behind inline skating and skateboarding. 25 From 1997 to 2001, an estimated 11 998 people aged 7 years and older with paintball game related injuries were treated in hospital emergency departments for an average annual rate of 4.5 per 10 000 participants.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 With 9.64 million paintball participants in the United States alone, paintball is the third most popular 'extreme' sport, behind inline skating and skateboarding. 25 From 1997 to 2001, an estimated 11 998 people aged 7 years and older with paintball game related injuries were treated in hospital emergency departments for an average annual rate of 4.5 per 10 000 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the participants started the game with eye protection but removed them because of fogging, discomfort, or paint on the lens or had the goggles accidentally dislodged while running. 2,3,5,6,12,14,16,17,19 In 1987, Martin and Magolan 4 reported the first case of eye injury despite the use of goggles. Their patient's goggles were driven into the globe from the force of impact of the paintball.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Fineman et al 16 published an analysis of 35 patients with paintball-related ocular injuries. They found that injuries sustained after 1995 were 5.8 times more likely to have occurred at a noncommercial site as compared with injuries sustained before 1995.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations